Anemia in Sudanese patients with chronic renal failure (CRF) and in patients undergoing chronic hemodialysis - Fathelrahman, MH (Bangladesh Journal of Medical Science, 2011)
Background: The term of anemia of chronic renal failure (CRF) in sufficiency refers to that anemia resulting directly from failure of the endocrine and excretory functions of the kidney and decreased production of erythropoietin by damaged kidneys. The serum erythropoietin level in patients with renal failure does not increase in response to the developing anemia, which is the primary cause of inadequate erythropoiesis. Aim: The purpose of our study was to examine, among patients with CRF, the combined association of CRF and anemia on adverse outcomes. Settings and Design: A hospitalized study using administrative data, we identified all patients hospitalized with CRF in IBN-Sena hospital and Khartoum teaching hospitals, Khartoum, Sudan. Materials and Methods: This was a retrospective cohort study of 500 patients having a diagnosis of chronic renal failure hospitalized and discharged between October 2007 to February 2010 from two Sudanese Teaching hospitals (Khartoum and IBN-Sena). All adult patients with chronic renal failure hospitalized for hemodialysis. Results: Hemoglobin level was recorded for 500 members (100%) of the cohort. The mean (SD) hemoglobin was 13.0 g/dL (2.2) range from 11.8 g/dL to 14.6 g/dL. On admission, an hemoglobin of ≥ 14 g/dL was found in 36.2% of the patients, 36.2% had an hemoglobin between 12 g/dL and 14 g/dL, 19.6% between 10 g/dL and 12 g/dL, and 8% ≤ 10 g/dL. The proportion of patients with CRF was associated with increasing anemia. Conclusion: The results obtained indicated the further evidence that the concomitant presence of either CRF or anemia increased the risk of dying in the hospital or of being readmitted within 30 days among patients hospitalized. The association persisted after controlling for other factors associated with adverse outcomes in these patients. Key words: Anemia, chronic renal failure. DOI: http://dx.doi.org/ 10.3329/bjms.v10i3.8357 BJMS 2011; 10(3): 152-158